Reducing inequality and insecurity: rethinking labor and employment policy for the 21st century - Appelbaum, Eileen (Washington, DC, 2012)
"In Good Jobs, Bad Jobs, Arne Kalleberg examines the institutional changes in the U.S. that led to a polarization of income and job quality, a rising share of poor quality jobs, and the increasing precariousness of work across the educational spectrum. He proposes reversing these developments through a new social contract that builds on the design principles that underlie flexicurity policies in the Netherlands and Denmark – flexicurity with an American face. This article discusses the roots and promise of flexicurity to address the problems Kalleberg has identified. It also examines the limits to flexicurity and proposes additional policies to fulfill this promise."